Upaya dalam Peningkatan Kompetensi Pendidik: Studi pada Dayah Darul Huda Lueng Angen Kabupaten Aceh Utara - Puspitasari, Maya; Prayogi, Eko; Hasibuan, Nurainun (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2023)
This research aimed to identify efforts to improve the competence of educators (teungku/guree) at Dayah Darul Huda Lueng Angen, North Aceh Regency. The research method used was a descriptive qualitative approach. Data were obtained through observation, in-depth interviews, and document analysis, which were analyzed through data condensation, data display, and verification/conclusion stages. The results showed that Dayah Darul Huda Lueng Angen plays a strategic role in traditional Islamic education in Aceh but still faces challenges in human resource development, especially in recruitment, competence, and the welfare of its educators. Dayah Darul Huda Lueng Angen has made several efforts to improve the competence of educators, including a program for teaching the